2013
DOI: 10.1186/1936-6434-6-25
|View full text |Cite|
|
Sign up to set email alerts
|

Early evolution of evolutionary thinking: teaching biological evolution in elementary schools

Abstract: Background: Evolution is considered the unifying concept in biology and is also a key theory underlying many areas of human knowledge. Teaching evolution from as early as kindergarten allows children to better understand concepts related with the biological world and prevents the development of negative feelings and misconceptions about the theory of evolution. However, evolution is absent from most of the educational curricula in the early school grades, even though some of its central concepts are common con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
2
24
0
2
Order By: Relevance
“…The other cohort of research, namely many of the studies focusing on engaging students in learning through activities, has shown that children can gain a simplified understanding of natural selection through such activities as games (Campos & Sá-Pinto, 2013) and virtual laboratories (Horwitz et al, 2013). These results are in line with findings from other researchers focusing on children's meaning making in science.…”
Section: Developing Methods To Introduce Evolution In Preschool Classsupporting
confidence: 69%
See 3 more Smart Citations
“…The other cohort of research, namely many of the studies focusing on engaging students in learning through activities, has shown that children can gain a simplified understanding of natural selection through such activities as games (Campos & Sá-Pinto, 2013) and virtual laboratories (Horwitz et al, 2013). These results are in line with findings from other researchers focusing on children's meaning making in science.…”
Section: Developing Methods To Introduce Evolution In Preschool Classsupporting
confidence: 69%
“…Researchers have made several attempts to find ways to teach evolution to young children. For example, children have been taught about evolutionary mechanisms through playful games (Campos & Sá-Pinto, 2013), computer games (Horwitz et al, 2013), hands-on activities (Nadelson et al, 2009), and storybooks (Browning & Hohenstein, 2015;Emmons et al, 2017;Emmons et al, 2016;Kelemen et al, 2014). In summary, this research has shown that children as young as five years old are able to learn simplified versions of multiple evolutionary concepts.…”
Section: Meaning Making Is Complexmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, active engagement in research related to the topic of study has been shown to further increase student interest in pursuing post-secondary studies in that field (reviewed by Kimbrough 1995). An outreach program by Campos & Sá-pinto (2013) designed to teach elementary school students about the fundamental concepts of evolution, used a series of simulations, drawing activities and group discussions. Though no metrics of learning were assessed, the authors described the students as engaged and able to perform the tasks asked of them.…”
Section: Introductionmentioning
confidence: 99%